2020
DOI: 10.5391/ijfis.2020.20.3.227
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Logic Expert System for Pricing Digital Services: The Case of Price Adjustment for a Mobile Service Provider

Abstract: As connected smart devices and terminals continue to grow along with digital content, data traffic of mobile service providers is also growing, and the price war in mobile markets is driving traffic growth without a commensurable increase in revenue. As a result, network capital expenditure (CAPEX) investment, quality of experience, and customer experience are under enormous pressure. In a competitive mobile market, strategic pricing may play an essential role in managing this pressure only if appropriate tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The fuzzy expert system (FES) algorithm is simple and involves only IF-THEN rules. Previous studies have reported the FES in detail [24][25][26][27][28][29][30][31][32][33] and is modeled to determine fault locations [34]. The FES was provided for location determination by considering the impedance values as inputs [35].…”
Section: Introductionmentioning
confidence: 99%
“…The fuzzy expert system (FES) algorithm is simple and involves only IF-THEN rules. Previous studies have reported the FES in detail [24][25][26][27][28][29][30][31][32][33] and is modeled to determine fault locations [34]. The FES was provided for location determination by considering the impedance values as inputs [35].…”
Section: Introductionmentioning
confidence: 99%